Nestor Makhno and rural anarchism in Ukraine, 1917-21 - Darch, Colin (London : Pluto Press, 2020)
Reveals a little-known history of 1917: the Ukrainian anarcho-communist Makhnovists.
8. The Bitter Politics of the Long Exile: Romania, Poland, Germany and France, 1921-34 -- 9. Why Anarchism? Why Ukraine? Contextualising Makhnovshchina -- Epilogue: The Reframing of Makhno for the Twenty-First Century -- Notes -- Index.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on March 3, 2022).
JSTOR
Keywords: Makhno, Nestor Ivanovich, -- 1889-1934.; Makhno, Nestor Ivanovich, -- 1889-1934; Anarchists -- Ukraine -- Biography; Ukraine -- History -- Revolution, 1917-1921.; Anarchistes -- Ukraine -- Biographies; Ukraine -- Histoire -- 1917-1921 (Révolution); HISTORY -- Revolutionary; Anarchists; Ukraine; 1917-1921; Biography; Biographies; History; Biographies; Biographies